Consequence Evaluation in Decision Analytic Models of Medical Screening, Diagnosis, and Treatment - Hershey, J. C. (Methods of Information in Medicine, 1974)
This paper examines the problem of assigning values, or utilities, to separate consequences in decision analytic models of medical screening, diagnosis, and treatment. Several important issues related to this problem are studied, and a number of methodologies proposed for various applications are reviewed in relation to these issues. Finally, suggestions for future research in this area are proposed.
Keywords: Medical Screening; Diagnosis; Therapy; Decision Analysis; Utility Theory